2017
DOI: 10.18054/pb.v119i3.4922
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of oral mucosal lesions among removable prosthesis wearers

Abstract: Background and purpose: The purposes of this study were to analyse the prevalence of oral mucosal lesions with an emphasis on oral regions and possible predictors for their occurrence among removable prosthesis wearers. night (p<0.001, OR 13.01; smoking (p=0.033, OR 4.532; OR 5.874;. The occurrence of tongue lesions was linked to age (p=0.042, OR 1.135;. Materials and methods: Conclusions:Increased care and frequent follow-ups need to be implemented among denture prosthesis wearers that are male, elderly, sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
5
0
4
Order By: Relevance
“…In this study, full denture wearers showed a higher prevalence compared with partial denture wearers (Table 5). Our results are in agreement with Bozdemir et al (2019) and contradict the results reported by Kovacevic (2017). In fact, complete dentures are mainly made of acrylic resin in which micropores may develop over time, allowing microorganisms to inhabit the prosthesis whereas partial prostheses are primarily made of metal, which does not allow the colonization of microorganisms.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In this study, full denture wearers showed a higher prevalence compared with partial denture wearers (Table 5). Our results are in agreement with Bozdemir et al (2019) and contradict the results reported by Kovacevic (2017). In fact, complete dentures are mainly made of acrylic resin in which micropores may develop over time, allowing microorganisms to inhabit the prosthesis whereas partial prostheses are primarily made of metal, which does not allow the colonization of microorganisms.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, participants with unmet need for prosthesis exhibited more oral mucosal lesions than those where the need was met (Table 5). In fact, different studies reported a higher oral mucosal lesion rate in patients individuals with old prosthesis compared with those with newer prosthesis one (Bozdemir et al, 2019;Ferreira et al, 2010;Kovacevic, 2017). The stability and integrity of the prosthesis are altered with time, resulting in traumatic lesions to the oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An ergonomically suitable product and physical equipment require that they be designed using the anthropometric data of the user population. Kovacevic et al (2010) noted that a properly designed vehicle seat reduces the driver's fatigue and provides safe traffic. Sedentary posture should be given additional consideration throughout the design process, especially when there are other manual tasks involving the use of force (Li and Haslegrave, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to air, noise pollution, fix posture of their working condition and whole body vibration puts them at the risk of stress and tension (Bhatt and Seema, 2012;Grösbrink et al, 2011). Morshidi and Norafneeza, (2019) and Kovacevic, et al, (2010) identified that incorrect sitting, unadjusted car seats, and non-use of safety belts are frequent causes of fatigue and accidents. Alongside these, a study conducted in Stockholm revealed that different working conditions influence stress levels.…”
mentioning
confidence: 99%